2019
DOI: 10.1002/mrd.23250
|View full text |Cite
|
Sign up to set email alerts
|

The Cxadr–Adam10 complex plays pivotal roles in tight junction integrity and early trophoblast development in mice

Abstract: Understanding preimplantation embryo development has important implications for assisted reproductive technologies (ARTs) after the introduction of in vitro fertilisation and embryo transfer because most embryonic losses occur during pre/peri‐implantation. Recent studies have shown that tight junctions (TJs) are important components for embryos to develop to the blastocyst stage. However, their biological function after cavitation has not been extensively studied. We examined TJ assembly focusing on coxsackiev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 45 publications
1
13
0
Order By: Relevance
“…In agreement with a previous study (Jeong et al, 2019), Cxadr KD resulted in retardation of blastocyst (52 ± 3%, Fig. 1A), and morula embryos treated with selective inhibition (SI) of Adam 10 also arrested and developed blastocyst (45 ± 6%, Fig.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…In agreement with a previous study (Jeong et al, 2019), Cxadr KD resulted in retardation of blastocyst (52 ± 3%, Fig. 1A), and morula embryos treated with selective inhibition (SI) of Adam 10 also arrested and developed blastocyst (45 ± 6%, Fig.…”
Section: Resultssupporting
confidence: 93%
“…The purpose of this study is to investigate the effect of defects of TJ complex/integrity on postimplantation embryo development and to expand our previous findings (Kwon et al, 2016a;Kwon et al, 2016b;Jeong et al, 2019) where CXADR interacts with ADAM 10 and they are required for AJ/TJ assembly during preimplantation development in pig and mouse. In line with previous studies (Kwon et al, 2016a;Kwon et al, 2016b;Jeong et al, 2019), we found that depletion of Cxadr and inhibition of 2006). Thus, the gradual weight gain after ET may reflect increased embryo and placental weight, but weight-loss for two consecutive days is attributed to loss of embryos because maternal body weight rapidly increased from around 2nd trimester onwards (Kulandavelu et al, 2006).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Proteins in this group included ADAM10, CPM, GPX3, and UBA52. ADAM10 is a metalloproteinase that may moderate tight junctions in trophoblastic cells, which is an essential component for the development of the embryo to the blastocyst stage [ 54 ]. CPM is a cell surface peptidase expressed in trophoblastic cells, which is involved in its differentiation and function [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…The number of DEGs in the other groups was too small to perform GO analysis. Notably, among 11 DEGs whose expression levels were higher in the TE of blastocysts with higher expectations of pregnancy, CXADR, CLDN10, and ATP1B were known to be involved in normal development [24][25][26] (see Discussion). These results provide a valuable list of genes for predicting pregnancy expectations in blastocysts.…”
Section: Identi Cation Of Genes Associated With Pregnancy Expectationmentioning
confidence: 99%